Green Business: A Brief Financial Profile of the Romanian Eco-Industry - Cristina Circa; Alina Almasan (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The objective of the paper is to outline an overview of the financial position and performance of the national eco-industry, based on a financial statements analysis performed on a significant sample of companies. The research focused on the most representative Romanian eco-industrial sectors, i.e. the pollution control technology sector, the waste management sector and the green energy sector. The time span included in the analysis was 2006-2012, while the selected financial ratios concerned the companies' performance and funding sources, as main factors defining their ability to remain on the market and in the same time promote sustainability in difficult times. As a main result, the research delivers a global picture over the business volume, profitability and efficiency, as well as over the solvability and the structure of the funding sources in the selected sectors, in a period within which the activity of the companies considered in the study was marked by two major events: the global financial crisis and the adhesion of Romania to the European Union.
Keywords: M41; 650; financial analysis; performance analysis; eco-industry; sustainability